2008
DOI: 10.1039/b702920a
|View full text |Cite
|
Sign up to set email alerts
|

MicroParticle photophysics illuminates viral bio-sensing

Abstract: The authors present an approach for specific and rapid unlabeled detection of a virus by using a microsphere-based whispering gallery mode sensor that transduces the interaction of a whole virus with an anchored antibody. They show theoretically that this sensor can detect a single virion below the mass of HIV. A micro-fluidic device is presented that enables the discrimination between viruses of similar size and shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 30 publications
0
69
0
Order By: Relevance
“…The method used to create the micro-particles with controlled internal chiral architectures presents great flexibility providing several advantages connected to the acquired optical and photonics capabilities and allowing to envisage novel strategies for the development of chiral colloidal systems and materials. © 2014 Author (s Micro and nano-scale particles have recently attracted considerable attention in several research areas, as optical trapping and manipulations, [1][2][3][4][5] microfluidics and optofluidics, [6][7][8][9][10] sensors, [11][12][13][14][15][16] photonics, photonics crystals, [17][18][19] colloidal and materials science. [20][21][22][23][24][25][26][27] Strategies to create multifunctional micro-particles even with dissymmetric properties, like Janus particles, have been successfully explored.…”
mentioning
confidence: 99%
“…The method used to create the micro-particles with controlled internal chiral architectures presents great flexibility providing several advantages connected to the acquired optical and photonics capabilities and allowing to envisage novel strategies for the development of chiral colloidal systems and materials. © 2014 Author (s Micro and nano-scale particles have recently attracted considerable attention in several research areas, as optical trapping and manipulations, [1][2][3][4][5] microfluidics and optofluidics, [6][7][8][9][10] sensors, [11][12][13][14][15][16] photonics, photonics crystals, [17][18][19] colloidal and materials science. [20][21][22][23][24][25][26][27] Strategies to create multifunctional micro-particles even with dissymmetric properties, like Janus particles, have been successfully explored.…”
mentioning
confidence: 99%
“…3,11 Specifically, we model a spherical resonator of radius r sphere ¼ 42.5 lm and toroidal resonator of major and minor radii r a ¼ 40 lm and r i ¼ 2.5 lm, respectively, so that the two geometries have equal outer radii. In the absence of convenient analytical expressions or approximations like those for the flow fields surrounding spheres and cylinders, the most effective method for solving the momentum balance and continuity equations (i.e., the Navier Stokes equations) for laminar flow around a toroid is to use numerical techniques.…”
Section: Applied Physics Lettersmentioning
confidence: 99%
“…From its inception theory indicated that although single protein detection was out of the question with a bare silica resonator due to intrinsic baseline noise and cavity leakage, human virus with a mass more than 1000 larger should be detectable [3]. Indeed individual virus particles were detected [4] under previously prescribed conditions [5]. The beauty of bio-nanoparticle detection in this way is that it is fully analytical; an accurate determination of the nanoparticle size is possible for particles pulled to the WGM's ring of light [6] by optical gradient forces [7].…”
Section: Introductionmentioning
confidence: 97%